HIV and Surgery for Degenerative Spine Disease: A Systematic Review - Farias, Frederico Arriaga Criscuoli; Dagostini, Carolina Matté; Falavigna, Asdrubal (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims The objective of this review is to evaluate the incidence of operative treatment, outcomes, and complications of surgery for degenerative spine disease (DSD) on human immunodeficiency virus (HIV) positive patients. Combined antiretroviral treatment led HIV patients to live long enough to develop many chronic conditions common in the uninfected population. Surgery for DSD is one of the most commonly performed neurosurgical procedures. However, the incidence of spine surgery for DSD in HIV-positive patients seems to be lower than that in uninfected individuals, although this has not been clearly determined.Methods A systematic search of the Medline, Web of Science, Embase, and SciElo databases was conducted. Only primary studies addressing DSD surgery on HIV-positive patients were included. Evaluated variables were rates of surgical treatment, surgical outcomes and complications, year of publication, country where study was conducted, type of study, and level of evidence.Results Six articles were included in the review from 1,108 records. Significantly lower rates of DSD surgery were identified in HIV-infected patients (0.86 per 1,000 patient-years) when compared with uninfected patients (1.41 per 1,000 patient-years). There was a significant increase in spinal surgery in HIV-positive patients over time, with a 0.094 incidence per 100,000 in the year 2000 and 0.303 in 2009. HIV-positive patients had very similar outcomes when compared with controls, with 66.6% presenting pain relief at a 3-month follow-up. Higher incidences of hospital mortality (1.6 vs. 0.3%; p < 0.001) and complications (12.2 vs. 9.5%, p < 0.001) were observed in HIV carriers.Conclusions HIV-positive individuals appear to undergo less surgery for DSD than HIV-negative individuals. Improvement rates appear to be similar in both groups, even though some complications appear to be more prevalent in HIV carriers. Larger studies are needed for decisive evidence on the subject.
Keywords: HIV; spine surgery; back pain; degenerative spine disease; systematic review